Analisis Faktor-Faktor yang Menyebabkan Ketidakdisiplinan Siswa di SD 058101 Sumber Jaya - Wahyu Adinda Wardani Lestari; Putri Nabillah; Nazmi Ayunestia Widyati; Bella Tricahayu; Nahdatul Amna (EduInovasi: Journal of Basic Educational Studies, 2023)
Discipline is something that is integrated within a person and even discipline is something that is integrated into human life that appears in daily behavior patterns both in the family, school and community. This study aims to describe the factors that cause low student discipline and the obstacles experienced in disciplining students of SDN 058101 Sumber Jaya, research using a descriptive qualitative approach. The research subjects were students of SDN 058101 Sumber Jaya. The object of research is the factors that cause low student discipline. Collecting data by observation, interviews, documentation. It can be concluded that the various forms are diverse. The most frequent violations committed by students are regarding the indiscipline of students who arrive late, do not complete assignments on time, do not pay attention to lessons, take out the trash on time and are not dressed neatly. Then there are several factors that cause student indiscipline, namely internal factors where internal factors are factors that come from within the student himself and external factors, which are factors that come from outside the student's self, for example the influence of the surroundingenvironment. Keywords: discipline, factors causing, student, SDN 058101 Sumber jaya